2009
DOI: 10.1128/jvi.02645-08
|View full text |Cite
|
Sign up to set email alerts
|

Replicative Capacity Differences of Thymidine Analog Resistance Mutations in Subtype B and C Human Immunodeficiency Virus Type 1

Abstract: In order to understand the impact of zidovudine resistance and thymidine analog mutations (TAMs) on subtype C human immunodeficiency virus type 1, we created mutants in subtype C reverse transcriptase (RT). The subtype B RT was placed in a subtype C backbone to act as a control. Mutants and wild-type (WT) virus were competed in a head-to-head competition assay to determine how different clones grew in the same culture. Different viruses were distinguished by sequence tags in nef and a quantitative-PCR assay. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The difference in viral DNA accumulation between viruses carrying RT from subtype B and C isolates may eventually determine the overall level of viral replication, that is consistent with the published data on subtype-associated effect of RT on viral replicative fitness [29]. …”
Section: Resultssupporting
confidence: 87%
“…The difference in viral DNA accumulation between viruses carrying RT from subtype B and C isolates may eventually determine the overall level of viral replication, that is consistent with the published data on subtype-associated effect of RT on viral replicative fitness [29]. …”
Section: Resultssupporting
confidence: 87%
“…The HIV subtype C molecular clone MJ4 was used as the backbone virus for all clones (30). The subtype B sample in this study is the RT from HXB2 (36), replacing the RT in MJ4 so that the viruses are identical except for RT (1). The consensus C sequence for RT from the Los Alamos HIV database (23) was used as the template to create the consensus C RT used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…They also showed that the TAM-2 mutant D67N/K70R/T215F had the slowest replication levels between both subtypes [25]. This might explain why D67N and K70R emerged first and then T215I was selected instead of 215F in 66% of replicates.…”
Section: Discussionmentioning
confidence: 97%